Proposisi dalam Matematika: Pemahaman Tentang Negasi Konjungsi, dan Disjungsi dan Penerapan Operasi Logika dalam Analisis Matematika - Prihaten Maskhuliah; Tita Mustikawati Selayar; Aulia Salsabila Putri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This article examines the concept of propositions in mathematics, which are statements referred to as (closed sentences, false, values, and true values). The discussion covers negation, or what is known as negation, as operations that have truth values and truth tables. In addition, this article examines conjunction, or compound propositions that are true. (the combination of two questions), which involves two propositions with either true or false values. Furthermore, this article also examines disjunction, which involves statements containing conjunctionand also has truth tables. The primary objective is to provide a concise yet comprehensive understanding of propositions as logical and mathematical concepts. In addition, this article examines conjunction, or compound propositions that are true. A conjunction involves two propositions that are combined using the logical operator